Carcinogen-mediated methotrexate resistance and dihydrofolate reductase amplification in Chinese hamster cells. - Kleinberger, T (1986)
We have investigated different parameters characterizing carcinogen-mediated enhancement of methotrexate resistance in Chinese hamster ovary (CHO) cells and in simian virus 40-transformed Chinese hamster embryo (C060) cells. We show that this enhancement reflects dihydrofolate reductase (dhfr) gene amplification. The carcinogens used in this work are alkylating agents and UV irradiation. Both types of carcinogens induce a transient enhancement of methotrexate resistance which increases gradually from the time of treatment to 72 to 96 h later and decreases thereafter. Increasing doses of carcinogens decrease cell survival and increase the enhancement of methotrexate resistance. Enhancement was observed when cells were treated at different stages in the cell cycle, and it was maximal when cells were treated during the early S phase. These studies of carcinogen-mediated dhfr gene amplification coupled with our earlier studies on viral DNA amplification in simian virus 40-transformed cells demonstrate that the same parameters characterize the amplification of both genes. Possible cellular mechanisms responsible for the carcinogen-mediated gene amplification phenomenon are discussed.